2012
DOI: 10.2215/cjn.00440112
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dialysis Modality with Risk for Infection-Related Hospitalization

Abstract: SummaryBackground and objectives Peritonitis is a well known complication of peritoneal dialysis (PD), whereas in hemodialysis (HD), bacteremia can be life threatening. Whether patients undergoing PD have higher risk than HD patients for infection-related hospitalizations (IRH) remains unknown.Design, setting, participants, & measurements A propensity score-matched retrospective cohort of patients undergoing long-term dialysis between January 2001 and December 2007 was assembled. Propensity scores were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 21 publications
4
52
1
1
Order By: Relevance
“…In contrast to the work by Lafrance et al (21), which reported a relative risk of 1.52 (95% CI, 1.34 to 1.74) for infection-related hospitalization, we did not find a higher rate from overall infection in PD. Verger et al (9) reported a higher risk of peritonitis on assisted PD, but the differences disappeared when PD nurses from the dialysis center regularly visited patients to supervise the home care nurses.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the work by Lafrance et al (21), which reported a relative risk of 1.52 (95% CI, 1.34 to 1.74) for infection-related hospitalization, we did not find a higher rate from overall infection in PD. Verger et al (9) reported a higher risk of peritonitis on assisted PD, but the differences disappeared when PD nurses from the dialysis center regularly visited patients to supervise the home care nurses.…”
Section: Discussioncontrasting
confidence: 99%
“…While overall survival was similar between both modalities (13), PD was associated with a higher risk of death from infection compared with HD (14). Similarly, we have previously found that rates of all-cause hospitalization were equivalent between dialysis modalities but that PD was associated with a 52% increased risk of overall IRH compared with HD (15). This suggests that the higher risk of IRH was partly compensated for by a reduced risk of other causes of hospitalization.…”
Section: Introductionmentioning
confidence: 51%
“…Using the same cohort, we have previously shown a similar risk of all-cause hospitalization between PD and HD patients (15). However, PD was related to a 52% increased risk of IRH compared with HD.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations